Gracián y la utilización de sus fuentes: deconstrucción e integración del Oráculo manual y arte de prudencia - Díez Fernández, J. Ignacio (Dicenda. Estudios de lengua y literatura españolas, 2008)
The difficulties in establishing the sources of the three hundred aphorisms contained in the Oráculo manual y arte de prudencia do not arise so much for lack of research, but rather from Gracian’s use of a very original writing approach that exceeds the normal generic boundaries of wisdom literature. Gracián goes beyond classic imitation by breaking down his hypothetical sources and rebuilding them into a new network of relations. The Oráculo manual does not reproduce the methodologies found in other wisdom books, since its aphorisms are better explained by a self referential system. Gracián offers a new knowledge, derived from a number of sources, that lends itself to multiple interpretations and that, like a complicated game, erases the influence of the past.